Analysis of Security Service Oriented Architecture (SOA) With Access Control Models Dynamic Level - Erick Fernando; Pandapotan Siagian (ICON-CSE, 2014)
Now we are moving towards the "Internet of Things" (IOT) in millions of devices will be interconnected with each other, giving and taking information provided within a network that can work together. Because of computing and information processing itself IOT core supporters, So in this paper introduces "Service-Oriented Computing" (SOA) as one of the models that can be used. Where's it at each device can offer functionality as a standard service [4]. In SOA, we can make the resources available to each other in the IOT together. However, a major challenge in these service-oriented environment is the design of effective access control schemes. In SOA, the service will be invoked by a large number, and at the same time authentication and authorization need to cross several security domains are always used. In this paper, we present the analysis of data safety suatua WorkflowBased Access Control Model associated oriented (WABAC) to troubleshoot problems that occur within a system integration. The analysis showed that the point system function model based integration system that is lower than the legacy model of SOA-based systems, by designing several services using WOA approach. In addition, we have observed that the integrated model can guarantee the quality of service, security and reliability main, by applying SOA approach when needed. Finally, experimental results have proved that the service can be run side by side seamlessly without performance degradation and additional complexity.